Analysis of forensic genetic parameters of 22 autosomal STR markers (PowerPlex® Fusion System) in a population sample from Bosnia and Herzegovina - Amela Pilav; Naris Pojskić; Abdurahim Kalajdžić; Anesa Ahatović; Mirela Džehverović; Jasmina Čakar (Taylor & Francis Group, 2020)
Background: Bosnia and Herzegovina is a multinational and multireligious country, located in the western part of the Balkan Peninsula. Migrations through history were a key factor in the genetic identity of the Bosnian-Herzegovinian population. Aim: To analyse genetic polymorphisms of 22 autosomal short tandem repeat (STR) loci in the population of Bosnia and Herzegovina and to compare STR allele frequencies for STR loci with the reference data for European populations. Subjects and methods: The study was conducted among 600 unrelated individuals from all regions of Bosnia and Herzegovina. Genotyping was performed using the PowerPlex® Fusion amplification kit. Allele frequencies and statistical parameters were calculated, as well as the genetic distance among analysed populations through the construction of a neighbor-joining dendrogram. Results: STR loci included in the PowerPlex® Fusion amplification kit showed high discriminatory power indicating their reliability for human identification and paternity testing. The neighbor-joining dendrogram based on the results of genetic distance analysis showed that the Bosnian and Herzegovinian population has the greatest genetic distance from Turkish and Hungarian populations and greatest similarity with Croatian, Slovenian, and Serbian populations. Conclusion: The results of this study strongly support the application of 22 autosomal genetic markers for paternity testing and personal identity testing and are in agreement with most previous human studies in the investigated human populations.